Morbidity Associated With Primary Hyperparathyroidism—A Population-based Study With a Subanalysis on Vitamin D - Soto-Pedre, Enrique; Lin, Yeun Yi; Soto-Hernaez, Jimena; Newey, Paul J; Leese, Graham P (The journal of clinical endocrinology and metabolism, 2023)
Abstract Context Primary hyperparathyroidism (PHPT) is associated with increased risk of morbidity and death, and vitamin D levels are a potentially confounding variable. Objective The aim of this study was to assess morbidity and mortality associated with primary hyperparathyroidism (PHPT). Methods In this population-based retrospective matched cohort study, data linkage of biochemistry, hospital admissions, prescribing, imaging, pathology, and deaths was used to identify patients across the region of Tayside, Scotland, who had PHPT from 1997 to 2019. Cox proportional hazards models and hazards ratios (HR) were used to explore the relationship between exposure to PHPT and several clinical outcomes. Comparisons were made with an age- and gender-matched cohort. Results In 11 616 people with PHPT (66.8% female), with a mean follow-up period of 8.8 years, there was an adjusted HR of death of 2.05 (95% CI, 1.97-2.13) for those exposed to PHPT. There was also an increased risk of cardiovascular disease (HR = 1.34; 95% CI, 1.24-1.45), cerebrovascular disease (HR = 1.29; 95% CI, 1.15-1.45), diabetes (HR = 1.39; 95% CI, 1.26-1.54), renal stones (HR = 3.02; 95% CI, 2.19-4.17) and osteoporosis (HR = 1.31; 95% CI, 1.16-1.49). Following adjustment for serum vitamin D concentrations (n = 2748), increased risks for death, diabetes, renal stones, and osteoporosis persisted, but not for cardiovascular or cerebrovascular disease. Conclusion In a large population-based study, PHPT was associated with death, diabetes, renal stones, and osteoporosis, independent of serum vitamin D concentration.